Бабинська культуроґенеза - Литвиненко, Р.О. (Археологія і давня історія України, 2021)
Розглядається проблема культуроґенези в археології на прикладі дніпро-донської бабинської культури. The problem of the Babyne Culture’s origin has
been repeatedly raised by Ukrainian scientists. Thus,
in the literature you can find about a dozen versions
of Babyne’s cultural genesis (Братченко 1971; 1976;
1977; 1985; 1995a; 1995b; 2006; Березанская 1979;
1986; Писларий 1983; 1991; Pâslaru 2006; Дергачев
1986; Ковалева 1981; 1987a; 1987b; Черняков 1996;
Отрощенко 1996; 1998; 2002; 2003; Grigoriev 2002;
Санжаров 2010; Іванова, Тощев 2018). About half of
these versions were born more as a result of the authors’
intuition than as a result of systematic, comprehensive
and painstaking research. The author of these lines
also devoted a series of publications to the problem of
Babyne’s cultural genesis. This article summarizes the
results of the author’s research of Babyne’s cultural
genesis, which is not presented in full, but only in its
key part — the origin of the primary of the structural
units of the Babyne Cultural Circle — Dnieper-Don
Babyne Culture (DDBC).
The basic source of research is burial mounds,
which, compared to settlements, are better and more
fully studied, are more mass, diagnostic in chronological
and cultural-taxonomic sense. The archeological
ensemble of Babyne cemeteries was initially divided
into structural elements at the level of mound construction,
burial structures, remains of the deceased,
funeral equipment, traces of additional ritual actions,
etc. The assessment of the structural components of
the DDBC cemeteries shows that this set of elements is
not homogeneous and can be divided into three groups,
different in origin: I) traditions; II) external influences;
III) innovation (figure).
I. Traditions are associated with the preceding local
cultural component, mostly the Donets-Don Catacomb
Culture and to a lesser extent the Ingul Catacomb
Culture: burial «packages», «sets of tools», quivers with
arrows, dice, animal «skins» («Head and Hooves»), certain
types of metal axes and knives, stone maces and
axes, wooden ware and boxes, wooden crooks, ceramic
ware from a triangle-parquet-fir decor, ceramic amphorae
and hemispherical bowls, faience beads with warts,
bone ring buckles, etc. (figure: I).
ІІ. External influences have no local roots in Eastern
Europe but find clear complex analogies in the
cultures / groups of the Early Bronze Age in Central
and South-Eastern Europe. All these effects relate to
certain features of the burial ceremony, the headset
jewelry and clothing decoration: gender opposition of
the dead, copper-bronze neck ring, arm-spirals, double
spiral pendants, spiral and tin tubes, disc plate with
punch ornament, hemispherical platelets with two
holes, pendant of Canis holes, buckles with a hook,
wrist-guards (figure: II). This subcomplex allows to
synchronize DDBC with the cultures of Central Europe
of the Reineke’s Br A1b—A2a.
III. Innovations include such components of the
cultural complex of DDBC, which can’t be associated
with local cultural substrate and external influences:
specific mound construction (long mounds, stone architecture),
the location of secondary graves in the northern
semicircle of the mound, wooden tombs and stone
cysts, specific ceramic vessels, original system of ornament-
signs, etc. (figure: III).
The three selected blocks are different in nature
and origins and are understood by us as constituent
elements of DDBC genesis. The basic substrate for
the formation of the DDBC was the aboriginal component
of the late Catacomb Culture, which began to
transform into the DDBC thanks to an external catalyst
from Central Europe (Unetice culture and related
groups). This impulse from Central Europe to Eastern
Europe can be linked to either migration or missionary
cultural leaders. It should be borne in mind that
these processes took place against the background of a
global climate catastrophe with its maximum around
2200 BC.